REIFICATION OF HEROISM IN CLINT EASTWOOD'S FLAGS OF OUR FATHERS MOVIE (2006): A MARXIST CRITICISM - KRISTIYANA, YUNI (2011)
The research is proposed to analyze reification of heroism in a film with the title Flags of Our Fathers with a Marxist Criticism. There are two objectives: the first is to analyze the film in term of structural element, and the second is to analyze the film based on a Marxist Criticism. The type of the research is descriptive qualitative. The primary data source that is used by the writer is Flags of Our Fathers movie and the script. Movie script is taken from a website. The secondary data are taken from the other sources which relate to this movie such as books, journals, and articles from the internet to support the main data. The method of collecting data is library research whereas the technique for analyzing is descriptive analysis. The result of the study shows as follows. First, based on structural analysis, the writer has successfully delivered the message from the stuctural elements. Each structural element correlates to each other and composes one unity. Second, based on a Marxist Criticism, Flags of Our Fathers is a story that appears reification of heroism of the government and society (bussinessmen) toward certain people called the heroes in World War II between the United States and Japan.